Challenges to conventional opinions on Qumran and Enoch issues - Heger, Paul, 1924- (Studies on the Texts of the Desert of Judah, 2012)
Some literary expressions in the Dead Sea Scrolls led scholars to allege that their authors professed a dualistic and deterministic worldview of Zoroastrian origin and that the omission of Moses and Sinai from the Enoch writings evinces that a segment in Jewish society marginalized the Torah, adopting Enoch's prophecies as its ethical guideline. This study challenges these allegations as utterly conflicting with essential biblical doctrines and the unequivocal beliefs and expectations of Qumran's Torah-centered society, arguing that scholars' allegations are erroneously based on interpreting ancient texts with a modern mindset and influenced by the interpreter's personal cultural background. The study interprets the relevant texts in a manner compatible with the presumed doctrines of ancient Jewish authors and readers.